Study Guide and Unit Mastery Program for Atkinson & Hilgard's introduction to psychology - Carlson, John G. (Wadworth/Thomson, 2003)
Each chapter contains learning objectives, fill-in-the-blank test items covering important names and each major sub-category, short answer questions for each major sub-category, essay questions and two sample end-of-chapter quizzes. Answers for all chapters are found at the back of the Study Guide